2017
DOI: 10.1210/jc.2017-00453
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-221-3p Regulates Angiopoietin-Like 8 (ANGPTL8) Expression in Adipocytes

Abstract: The inflammation-induced miR-221-3p regulates ANGPTL8 expression in adipocytes. This miRNA impact may become especially prominent under pathologic conditions such as morbid obesity, putatively contributing to the impaired AT lipid metabolism in metabolic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 50 publications
5
30
0
Order By: Relevance
“…A recent study showed that ANGPTL8 was downregulated in adipocytes due to the inflammation regulation; however, the mechanisms of ANGPTL8 in regulating inflammation have not been investigated. 58 In our study, a higher level of ANGPTL8 expression was detected in the more degenerative NP tissues and ANGPTL8…”
Section: Imbalance Between Ecm Metabolism and Inflammatory Responsesupporting
confidence: 55%
“…A recent study showed that ANGPTL8 was downregulated in adipocytes due to the inflammation regulation; however, the mechanisms of ANGPTL8 in regulating inflammation have not been investigated. 58 In our study, a higher level of ANGPTL8 expression was detected in the more degenerative NP tissues and ANGPTL8…”
Section: Imbalance Between Ecm Metabolism and Inflammatory Responsesupporting
confidence: 55%
“…miR-27a-3p plays an important role in adipogenesis [62], regulation of fat function [63], increase in glycogen storage [64], and regulation of insulin sensitivity [65]. miR-221-3p may affect insulin sensitivity and lipogenesis by regulating ANGPTL8 [66,67]. miR-222-3p mediates the apoptosis of adipocytes in visceral fat from obese individuals and may attenuate hyperglycemia in a diabetic mouse model [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL8/betatrophin has shown its considerable association with diabetes and obesity as well as various metabolic biomarkers in glucose and lipid homeostasis (Wang et al 2016;Abu-Farha et al 2017). This hormone is reported to be highly enriched in human and mouse liver and adipose tissues (Chen et al 2019;von Loeffelholz et al 2017;Catalano-Iniesta et al 2020;Akimoto et al 2019;Mysore et al 2017). Previous studies focused on the roles of ANGPTL8 as a hormone that directly works on the endocrine system, while hardly any evidence showed that external mediators are involved in these processes (Siddiqa et al 2017;Wang et al 2016;Abu-Farha et al 2017;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The angiogenin-like protein family includes eight members structurally similar to angiogenin and widely participate in the regulation of lipid metabolism, inflammation, haematopoietic stem cell activity and cancer cell invasion. ANGPTL8 is highly enriched in the human liver and various adipose tissues, whose levels were much lower in the other tissues, and recent studies suggested that ANGPTL8 showed similar tissue distribution in mice (Chen et al 2019;von Loeffelholz et al 2017;Catalano-Iniesta et al 2020;Akimoto et al 2019;Mysore et al 2017). ANGPTL8 has been reported to play a significant role in various metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%